Respostas

2014-08-02T15:53:14-03:00
Nesse caso não seria necessário a substituição, veja:
 \int\ { \sqrt{ x^{3} }-4 x^{2}  } \, dx = \int\ {\sqrt{ x^{3} }} \, dx -\int\ {4 x^{2}} \, dx  \\  \\  \int\ { x^{ \frac{3}{2} } } \, dx -4 \int\ { x^{2} } \, dx =  \frac{ x^{ \frac{3}{2}+1 } }{\frac{3}{2}+1} - 4. \frac{ x^{3} }{3}  \\  \\  \frac{ x^{ \frac{5}{2} } }{ \frac{5}{2} } -  \frac{4 x^{3} }{3} =  \frac{2 x^{ \frac{5}{2} } }{5}-  \frac{4 x^{3} }{3}= \frac{2 \sqrt{ x^{5} } }{5} -  \frac{4 x^{3} }{3} + C